Description of Hemoglobin, Hematocrit, Erythrocyte Count and Erythrocyte Indices in Chronic Kidney Disease Patients - Rosmala, Mila Ashri; Suryanto; Anggraeni, Rosmita (Jurnal Kesehatan Cendikia Jenius, 2025)
Chronic kidney failure is caused by abnormal kidney function and will affect the body's system processes. Chronic kidney failure is the 12th leading cause of death in the world with a death rate of 163,275 per year. In Indonesia, the prevalence is 0.38% or 3.8 per 1,000 population. In Yogyakarta, it increased from 0.3% (2013) to 0.43% (2018). Chronic kidney failure patients undergoing hemodialysis often experience anemia due to decreased production of the hormone erythropoietin. Anemia is generally normocytic normochromic, but there are also microcytic hypochromic and macrocytic. This study describes the levels of hemoglobin, hematocrit, erythrocytes, and erythrocyte indices based on age and sex at PKU Muhammadiyah Gamping Hospital using descriptive observational methods and medical record data from hemodialysis patients. The majority of respondents were male (71.2%). Most patients based on hemoglobin levels experienced mild anemia, as many as 27 patients (61.4%) with an average of 9.45 ± 1.53 g / dL. Hematocrit 30-40% in 23 patients (52.3%) with an average of 29.57 ± 5.19%. All patients had low erythrocytes with an average of 3.33 ± 0.72 million / µL and some patients (86.4%) experienced normocytic normochromic anemia. It was concluded that patients with chronic kidney failure often experience anemia because the production of the hormone erythropoietin decreases, causing the number of red blood cells to decrease even though their shape remains normal. Suggestions for further research are to find the exact cause and appropriate treatment so that the condition improves.